The microbial flora associated with oral carcinomas - Byakodi, Raghavendra; Krishnappa, R; Keluskar, Vaishali; Bagewadi, Anjana; Shetti, Arvind (Quintessence international (Berlin, Germany : 1985), 2011)
Changes in the microbial flora on the oral mucosa after cancerous alteration may lead to both local and systemic infections. In this study, we assessed the microbial flora associated with the surfaces of oral squamous cell carcinoma. A comparative evaluation of these microbial contents was made with that of the contralateral healthy mucosa and control (healthy) mucosa. We also assessed the microbial flora from the saliva culture in subjects with oral squamous cell carcinoma and healthy controls. The case control study was made up of 30 subjects with oral squamous cell carcinoma as the study group; 30 healthy age-, sex-, habit-, and dentition-matched subjects served as the control group. In the study group, microbial samples were collected from the carcinoma site, contralateral healthy mucosa, and saliva, whereas in the control group, samples were collected from the healthy mucosa and saliva. These samples were stored on ice and subsequently transported to the laboratory in 2 mL of thioglycollate transport media, where the microbial cultures were carried out. Oral squamous cell carcinoma sites harbor significantly more microbial flora (bacteria and yeasts) compared to those of healthy mucosa (control group). The microbial flora predominantly isolated from the carcinoma site were Streptococcus species, Staphylococcus species, Moraxella species, Enterococcus feacalis, Aerobic spore bearers, Klebsiella species, Citrobacter species, Proteus species, Pseudomonas species, and Candida albicans. The median number of colony forming units (CFU)/mL at carcinoma sites (3.85 x 105 CFU/mL) was significantly higher than that of the healthy mucosa (0.571 x 105 CFU/mL; P = .0000, Wilcoxon nonparametric test). Similarly, in saliva of carcinoma subjects, the median number of CFU/mL (2.408 x 105 CFU/mL) was significantly higher than that of saliva in control subjects (0.78 x 105 CFU/mL; P = .0000, Wilcoxon nonparametric test). The present study clearly indicates that the subjects with oral squamous cell carcinoma harbor significantly more microbial flora. Emphasis has to be given to preventing microbial flora in the oral cavity and treating these patients with appropriate antimicrobial agents, thus reducing their morbidity.